Pemanfaatan Grafis Dan Promosi Produk Aplikasi Canva Untuk Desain Pada Kopwan Atsiri Citayam Bogor - Eva zuraidh; Eko Setia Budi; Ade Priyatna; Sanwani; Jajang Abdul Jabar; Muhammad Rizki; Darmawan; Iqbal Ubaidillah; Dwi Satria Nugraha; Vitria Margharet (Akademi Farmasi YPPM Mandiri, 2022)
Atsiri Citayam Women's Cooperative was founded on December 11, 2011. A year later, Atsiri Citayam Women's Cooperative already has NIK 3201220040001 with Legal Entity Number: 518/277/BH/KPTS/DISKOPERINDAG/VI/2012 exactly on April 18, 2012. When viewed from the type In its business, this cooperative is included in the type of consumer cooperative that serves savings and loans and the sale of basic necessities. The number of members of this cooperative is 90 people consisting of various work backgrounds, including MSME entrepreneurs. The existence of regular meetings is used as an event to maintain friendship and exchange information, especially for MSME entrepreneurs. Limited understanding of the use of technology, namely online digital products. Therefore, Nusa Mandiri University carried out Community Service in the form of training on the Use of Canva Applications for Graphic Design and Product Promotion at the Bogor Citayam Atsiri Kopwan. With this training, they can help the women of the Atsiri Citayam Bogor Women's Cooperative in using the Canva application as a digital media.